Some results for a class of conformable fractional dynamic equations on time scales - Zheng, Bin (IJRDO- Journal of Educational Research, 2019)
In this paper, we discuss a class of fractional dynamic equations with damping term on time scales in the teaching of the college course Mathematical Physics Equations, and derive some results for it. The obtained results can be used in the research of oscillation properties for this kind of equationson time scales.